MARKETING FOR SEED-STAGE INNOVATIVE STARTUP - B. Tokarev (Вестник университета, 2018)
The proposed material is a logical continuation of publications on the marketing of innovative startups. The article discusses the stage when innovative product is developing. Marketing of this stage is based on Minimum Viable Product develop, and on searching and researching the future consumers. The author proposes the name of this type of marketing - marketing of innovation. It is shown that the prepared product to launch must have limited functionality, and is not brought to perfection. But this product should be required to pass a variety of testing, from conceptual to actual use by consumers. Key element of this startup stage is product testing by future customers. Article`s attention is addressed to methods for finding and communicating with consumers.